2017
DOI: 10.1515/jim-2017-0100
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Mobilization and Harvesting Failure in Case of Heavily Pretreated Patients

Abstract: Background: High-dose chemotherapy and autologous stem cell transplantation have become a standard curative treatment in various hematologic malignancies. Many factors can affect the success of mobilization and hematopoietic stem cell harvesting. Aim: The aim of this study was to analyze factors that lead to mobilization failure. Material and Methods: We conducted a retrospective study on 19 patients with failure of stem cell harvesting. All patients were administered high doses of GCS-F (filgrastim, 15 μg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the study included patients with various types of hematological malignancies, and the results found that the highest mobilization failure occurred in non-Hodgkin lymphoma (42%, n = 8), Hodgkin lymphoma (37.5%, n = 6), and multiple myeloma (21%, n = 4). 15 Being that autologous stem cell therapies can be a curative option for patients with various hematological cancers, further studies on the cause and factors associated with failure to harvest stem cells, as well as methods for improvement are essential.…”
mentioning
confidence: 99%
“…Moreover, the study included patients with various types of hematological malignancies, and the results found that the highest mobilization failure occurred in non-Hodgkin lymphoma (42%, n = 8), Hodgkin lymphoma (37.5%, n = 6), and multiple myeloma (21%, n = 4). 15 Being that autologous stem cell therapies can be a curative option for patients with various hematological cancers, further studies on the cause and factors associated with failure to harvest stem cells, as well as methods for improvement are essential.…”
mentioning
confidence: 99%